Cameron Center Market and Shops - Huddle's The Springs Restaurant Interior Perspective - William F. Cody::::::::: (1957)
Cameron Center Market and Shops - Huddle's The Springs Restaurant Interior Perspective Drawing, commercial, Job # 5901, 1957-1958